CONCEPTUAL FOUNDATIONS OF MARKETING ORGANIZATION AND LOGISTICS MANAGEMENT IN AGRIBUSINESS - Bekmatovich, Djurayev Bekzod; Egamkulovich , Utapov Nematullo (PT. Antis International Publisher, 2024)
Objective: This study aims to explore the impact of marketing and logistics systems on the efficiency of agricultural product production, storage, and sales, focusing on the challenges faced by agricultural producers in Uzbekistan. Methods: The research employs a systematic analysis of the agricultural supply chain, evaluating the role of marketing and logistics in managing the flow of goods, determining production volumes, and assessing market capacities. Data is gathered through literature review, case studies, and qualitative analysis of existing agricultural practices. Results: The findings highlight significant inefficiencies in the current agricultural logistics system, where the lack of proper marketing strategies and logistics infrastructure leads to high production and transportation costs, imbalances in consumer markets, and low competitiveness. The study identifies key areas where improvements in the marketing-logistics framework can reduce costs by 10-15%, enhance production planning, and better align supply with consumer demand. Novelty: This research introduces a comprehensive approach to integrating marketing and logistics systems in agricultural production, emphasizing the importance of strategic coordination between resource suppliers, producers, and market demands. It provides insights into developing a more efficient, market-responsive agricultural sector in Uzbekistan